2019
DOI: 10.1051/matecconf/201927606006
|View full text |Cite
|
Sign up to set email alerts
|

Study of struvite crystallization from fertilizer industry wastewater by using fluidized bed reactor

Abstract: The fertilizer industry produces wastewater containing 9815 mg/L of phosphates and 2558 mg/L of ammonium, which may cause eutrophication if untreated. Wastewater that contains a large amount of phosphate can become a potential source of phosphate which is depleting on a global scale. Fluidized bed reactors are an effective method of phosphate recovery by producing struvite crystals. This study evaluates the effects of the upflow velocity on the performance of the fluidized bed and analyzes the struvite that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As shown in Table 2 , increasing the recirculation ratio in an FBR can increase phosphate and ammonium removal [ 21 ]. Warmadewanthi and Bachtiar reported that decreasing the hydraulic loading rate to 1.2 L/min would reduce phosphate and ammonium removal by 1% [ 22 ]. The hydraulic loading rates of 0.39, 0.59, and 0.79 L/min of phosphate removal without recirculation were 48.4%, 48.5%, and 48.62%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 2 , increasing the recirculation ratio in an FBR can increase phosphate and ammonium removal [ 21 ]. Warmadewanthi and Bachtiar reported that decreasing the hydraulic loading rate to 1.2 L/min would reduce phosphate and ammonium removal by 1% [ 22 ]. The hydraulic loading rates of 0.39, 0.59, and 0.79 L/min of phosphate removal without recirculation were 48.4%, 48.5%, and 48.62%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Sustainable development and environmental preservation through production recovery purposes to use wastes as another potential in the form slow-release fertilizers low metal content compared with those released from phosphate rocks [ 15 , 20 ]. Factors that affect the phosphate crystallization process include pH [ 5 ], molar ratio of Mg 2+ , NH 4+ , and PO 4 3− [ 15 ], ion content in impurities [ 21 , 22 ], recirculation, and the precipitant used [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation